2016
DOI: 10.1115/1.4032185
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Measurements of Periodic Effects in a Transonic Compressor With Casing Treatments

Abstract: Application of nonaxisymmetric casing treatments (CTs) can extend the operating range of a transonic compressor significantly. Recent CT designs have proven successful at achieving operating range extension without efficiency loss under design conditions. Two different CT designs were investigated on a high-speed one and a half stage test rig using extensive instrumentation. The stage setup is representative of the front stage of a modern high-pressure compressor. Results of particle image velocimetry (PIV) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…This is especially the case for high circumferential Mach numbers. Similar effects were reported by Brandstetter [6] in his experiments with an axial compressor. This paper presents:…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is especially the case for high circumferential Mach numbers. Similar effects were reported by Brandstetter [6] in his experiments with an axial compressor. This paper presents:…”
Section: Introductionsupporting
confidence: 89%
“…While early attempts to design CTs were based on analytic considerations and test experiences, the progress in 3D CFD and optimization techniques enables new improvement possibilities. Good examples are the published CT simulation and test results by Streit [5] and Brandstetter [6]. The effect of the herein developed and investigated CT is limited to the blade tip region and it is supposed to only act if the rotor is highly throttled close to its operation limit.…”
Section: Introductionmentioning
confidence: 97%
“…Owing to the outstanding capacity of improving the compressor stability, the emphasis is laid on the application and exploration of axial slots [3][4][5][6][7][8] and axial skew slots [9][10][11][12][13][14][15][16] in most of the slot CT investigations. Wilke and Kau 3 performed a numerical investigation of axial slot CT on a transonic axial flow compressor, where the result shows that at 88% design speed, axial slot obtains the 6.5% decrease for the stall mass flow rate with the 5% decrease for the maximum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Casing treatment is found to be an effective passive control method for the instability occurring in the rotor tip since the 1950s. The researchers tested a mass of geometries on different test rigs in the past decades (Bailey and Voit, 1970;Koch, 1970;Brandstetter et al, 2015). The experimental results showed that the casing treatment extended the stall margin but at the cost of efficiency loss.…”
Section: Introductionmentioning
confidence: 99%